UPAYA MENINGKATKAN KOMPETENSI MENULIS MELALUI MODEL PEMBELAJARAN TEMATIK - Dasmawarti, Dasmawarti (STKIP Melawi, 2017)
Abstract : The purpose of this research is the application of thematiclearning model to improve the competence of students in grade I wrote aState Elementary School 08 Muara Pawan Ketapang. Subjects werestudents of class I SDN 08 Muara Pawan Ketapang many as 21 students.The research object is the competence of the student's writing andimplementation of thematic learning model. The method used in thisresearch is a classroom action research methods sasaranannya researchersas teachers and students of the first grade SDN 08 Muara PawanKetapang.Results of the study are as follows: (1) In the first cycle ofwriting competence of students of class I SDN 08 Muara Pawan based onthe results of the test write 67% of the number of students has reached thecriteria set the gain value ≥70 upwards. While in the second cycle writingcompetence of students of class I SDN 08 Muara Pawan increased by23% to 90%. (2) The effectiveness of the implementation of thematiclearning model is based on the observation of the learning process ofteachers in the first cycle is 75% and increased by 10% so that the secondcycle to 85%. Thus the thematic learning model when applied properlyeffective influence on improving the competence of the students' writingclass I SDN 08 Muara PawanKeywords: Improved writing competence, thematic learning modelAbstrak : Tujuan penelitian ini adalah penerapan model pembelajarantematik untuk meningkatkan kompetensi menulis siswa kelas I SekolahDasar Negeri 08 Muara Pawan Ketapang. Subyek penelitian adalah siswakelas I SDN 08 Muara Pawan Ketapang sebanyak 21 siswa. Sedangkanobyek penelitian adalah kompetensi menulis siswa dan penerapan modelpembelajaran tematik. Metode yang digunakan dalam penelitian ini adalahmetode penelitian tindakan kelas dengan sasaranannya peneliti sebagaiguru dan siswa kelas I SDN 08 Muara Pawan Ketapang. Hasil penelitianadalah sebagai berikut: (1) Pada Siklus I kompetensi menulis siswa kelas ISDN 08 Muara Pawan berdasarkan hasil tes menulis sebesar 67% darijumlah siswa telah mencapai kriteria yang ditetapkan yakni memperolehnilai ≥70 ke atas. Sedangkan pada siklus II kompetensi menulis siswakelas I SDN 08 Muara Pawan mengalami peningkatan sebesar 23%menjadi 90%. (2) Efektivitas penerapan model pembelajaran tematikberdasarkan hasil observasi proses pembelajaran guru pada siklus Imencapai 75% dan mengalami peningkatan sebesar 10% sehingga padasiklus II menjadi 85%. Dengan demikian model pembelajaran tematik apabila diterapkan secara baik dan benar berpengaruh efektif terhadappeningkatan kompetensi menulis siswa kelas I SDN 08 Muara PawanKata Kunci: Peningkatan kompetensi menulis, model pembelajarantematik